The benefits of Functional Movement Screen in judo (Revista de Artes Marciales Asiáticas, 2019)
With the development of screening methods, simple screening tools could commonly be used to assess movement quality in real-world conditions.  One of those methods is the functional movement screen (FMS), that was developed to helps determine the fundamental movement patterns of an individual. FMS test was administered to 9 elite judokas aged 22 ± 4.24 years, height 176.44 ± 7.44 and weight 79.44 ± 15.92 kg. The overall FMS score was 17.56 ± 1.59. No significant asymmetries were noted in the bilateral test. The lowest score was achieved in shoulder mobility 1.89 ± 0.6 which represent and issue that needs to be addressed to prevent the occurrence of injuries. Overall the FMS testing could be a beneficial tool to strength and conditioning coaches in judo, especially in the preseason to assess the functional movement status of judo athletes and to address any issues that could be identified. It represents a fast and affordable screening tool, but it needs to be administered by a qualified assessor. The data of this study could serve as a reference score to other FMS research in judo or other combat sports or martial arts.